Long- and short-term outcomes of early gastric cancer after endoscopic resection: a retrospective study from China - Zhang, Qing-Wei; Chen, Jin-Nan; Tang, Zhao-Rong; Gao, Yun-Jie; Ge, Zhi-Zheng; Li, Xiao-Bo (Endoscopy International Open, 2021)
Background and study aims The aim of the study was to evaluate short- and long-term outcomes of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) in China because no study has yet been conducted to confirm its effectiveness in EGC in China.Patients and methods A total of 570 EGC samples from 537 patients were collected for evaluation of en bloc, complete, and curative resection using ESD. Data from 302 patients with at least 3 years of active follow-up were collected for analysis of recurrence of EGC and occurrence of metachronous GC (MGC). Short- and long-outcomes of mixed-type and pure differentiated EGC were also compared.Results En bloc resection rates of 96.0 %, 98.7 %, and 95.2 %, complete resection rates of 91.2 %, 96.6 % and 90.8 %, and curative resection rates of 83.0 %, 96.2 % and 88.2 % were achieved in all EGCs included in the study, those with absolute indication, and those with expanded indication, respectively. As a long-term outcome, recurrence was observed in 1.3 % of patients, 3-year and 5-year recurrence rates being 0.7 % and 1.2 %, respectively. Thirteen patients (4.3 %) exhibited MGCs during follow-up, all of which were resected in a second ESD. Conclusions The effectiveness of ESD for EGC in China was confirmed, with satisfactory short- and long-term outcomes. With scheduled follow-up, the outcomes for mixed-type EGC can be similar to those for pure differentiated EGC after complete resection without development of lymphovascular invasion.